If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -1 = 0.5x + 4 Reorder the terms: -1 + 0.3x = 0.5x + 4 Reorder the terms: -1 + 0.3x = 4 + 0.5x Solving -1 + 0.3x = 4 + 0.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5x' to each side of the equation. -1 + 0.3x + -0.5x = 4 + 0.5x + -0.5x Combine like terms: 0.3x + -0.5x = -0.2x -1 + -0.2x = 4 + 0.5x + -0.5x Combine like terms: 0.5x + -0.5x = 0.0 -1 + -0.2x = 4 + 0.0 -1 + -0.2x = 4 Add '1' to each side of the equation. -1 + 1 + -0.2x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + -0.2x = 4 + 1 -0.2x = 4 + 1 Combine like terms: 4 + 1 = 5 -0.2x = 5 Divide each side by '-0.2'. x = -25 Simplifying x = -25
| 2y-5n= | | 24+8x=-96 | | -4K+3=-13 | | 10x+61=-59 | | 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 | | 7x-x=-16-2x | | -7r-8-5r=-13-7r | | 9x+45=100 | | f(x)=(x^7-4x^6)*(x+3)*(x-2) | | 9x+36=100 | | 12+3m=7m-2m | | 8x+32=100 | | v+4=-12+1-v-1 | | 10=4-5n+4n | | 7x+28=100 | | 7x+21=100 |